Effect of artificial lung fiber bundle geometric design on micro‐ and macro‐scale clot formation - Angela Lai; Natsuha Omori; Julia E. Napolitano; James F. Antaki; Keith E. Cook (Wiley, 2024)
Abstract The hollow fiber membrane bundle is the functional component of artificial lungs, transferring oxygen to and carbon dioxide from the blood. It is also the primary location of blood clot formation and propagation in these devices. The geometric design of fiber bundles is defined by a narrow set of parameters that determine gas exchange efficiency and blood flow resistance, principally: fiber packing density, path length, and frontal area. These same parameters also affect thrombosis. This study investigated the effect of these parameters on clot formation using 3D printed flow chambers that mimic the geometry and blood flow patterns of fiber bundles. Hollow fibers were represented by an array of vertical micro‐rods (380 μm diameter) arranged with three packing densities (40%, 50%, and 60%) and two path lengths (2 and 4 cm). Blood was pumped through these devices corresponding to three mean blood flow velocities (16, 20, and 25 cm/min). Results showed that (1) clot formation decreases dramatically with decreasing packing density and increasing blood flow velocity, (2) clot formation at the outlet of the fiber bundle enhances deposition upstream, and consequently (3) greater path length provides greater clot‐free fiber surface area for gas exchange than a shorter path length. These results can help guide the design of less thrombogenic, more efficient artificial lung designs.